P033 EFFICACY OF MIRIKIZUMAB ON HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH ULCERATIVE COLITIS: A RANDOMISED, DOUBLE-BLIND, CONTROLLED, PHASE 2 STUDY. (7th February 2019) - Sandborn, William J; Ferrante, Marc; Bhandari, Raj; D'Haens, Geert; Berliba, Elina; Feagan, Brian G; Klekotka, Paul; Laskowski, Janelle; Durante, Michael; Tuttle, Jay L; Naegeli, April
Abstract: Introduction: The efficacy and safety of mirikizumab (miri), an IL-23p19 antibody, has been evaluated in moderate-to-severe ulcerative colitis (UC) in a phase 2, randomized, double-blind, placebo (pbo)-controlled trial (AMAC, NCT02589665; presented at DDW 2018). Miri demonstrated efficacy on multiple measures in the 12-week induction treatment. Aims and Methods: This analysis evaluated the effects of miri on health-related quality of life (HRQoL) in patients with UC. Patients with moderate-to-severe UC (Mayo score 6-12; Endoscopic subscore ≥2) were randomised 1:1:1:1 to receive intravenous miri 50 mg (N=63) or 200 mg (N=62), both with possible exposure-based increase (2-12 fold or 1.5-3 fold, respectively, to a maximum 600 mg dose), or fixed dose miri 600 mg (N=61), or pbo (N=63) at Weeks 0, 4, and 8. Patients could receive oral 5-aminosalicylic acid (ASA), corticosteroids (≤20 mg/d prednisone equivalent), or thiopurines; must have failed ≥1 conventional UC therapy; and were either naïve to or had prior exposure to biologics. HRQoL was measured by the Inflammatory Bowel Disease Questionnaire (IBDQ) and evaluated using a mixed model repeated measures (MMRM) analysis. The percentage of patients at Week 12 with clinical response, 1 endoscopic healing, 2 IBDQ total score ≥170, and IBDQ improvement ≥16 were also assessed. Results: As early as Week 4, and continuing through Week 12, IBDQ total scores improved versus baseline and versus pbo across all miri groups except miri 50 mg versus pbo at Week 12 (Table). At Week 12, the proportions of patients with IBDQ total score ≥170 were higher with miri 50 mg, 200 mg, and 600 mg than pbo (44%, 56%, 54% vs. 30%, respectively) and higher proportions of miri- than pbo-treated patients had improvements ≥16 points from baseline in IBDQ total score. At Week 12, clinical response and endoscopic healing rates were greater for miri 50 mg and 200 mg versus pbo (Table). Conclusion: Induction treatment with miri was associated with HRQoL improvement in patients with UC. These are the first data evaluating the effects of an IL-23p19 antibody on the HRQoL of patients with UC.